High-accuracy virtual testing of air conditioner’s digital twin focusing on key material’s deformation and fracture behavior prediction - Shaohua Fu; Zhenping Wan; Weifeng Lu; Huaican Liu; Peng’e Zhang; Bo Yu; Jianming Tan; Feng Pan; Zhigang Liu (Scientific Reports, 2022)
Abstract The concept of digital twin has been introduced for some time, yet one fundamental element of digital twin, digital material, has not been thoroughly studied. To interact with the physical product, the digital twin should always truthfully reflect the responses under various stimuli. In this paper, the deformation and fracture behavior of high impact polystyrene (HIPS) under the influencing factors of strain rate and stress triaxiality are studied to construct the material’s digital model. A digital twin of air conditioner product is further built and tested under virtual drop test. Comparing to experimental results, the acceleration curve, crazing induced whitening and the fracture events can all be captured by the digital twin. Our work demonstrates the importance of material characterization as an essential step to construct an accurate digital twin and shows a promising future of digital twin in virtual testing to replace traditional “trial and error” experiments.